Novinky v morfologii zil dolní koncetiny - Riedlová, J; Smrzová, T (Rozhledy v chirurgii, 2008)
This comprehensive article notifies on the latest information concerning the morphology of the lower extremity veins, including their anatomical terminology. As a consequence of vehement development of the diagnostic and therapeutic techniques, the more detailed knowledge of anatomy, terminology, venous system variants and venous wall structure is necessary both for the phlebologists, sonographists and for the surgeons and cardiosurgeons. The histological part brings information about the content of collagen and elastin fibers in all layers of the superficial veins wall and about the arrangement of the vasa vasorum in both normal and varicose vena saphena magna. The anatomical-terminological part enlightens the variability of the superficial venous system of the lower extremity and the completion of the terminology of some superficial and deep veins, veins of the pelvis and perforating veins. The simple and clear anatomical terminology is the base for easy and non-problematic communication and discussion between inland and foreign specialists.
Keywords: terminologie jako téma; Terminology as Topic; lidé; vény; Veins; dolní končetina; Lower Extremity; Humans